2015
DOI: 10.1017/s1366728915000279
|View full text |Cite
|
Sign up to set email alerts
|

The same or different: An investigation of cognitive and metalinguistic correlates of Chinese word reading for native and non-native Chinese speaking children

Abstract: We investigated cognitive and metalinguistic correlates of Chinese word reading in children with L2 Chinese learning experience and compared these to those in L1 Chinese speaking children. In total, 102 third and fourth grade children were recruited for the study. We examined a range of Chinese and English word reading related cognitive and metalinguistic skills. Compared to the native Chinese speaking group (NCSS), the non-native Chinese speaking group (NNCS) only performed better in English vocabulary knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 81 publications
8
38
1
Order By: Relevance
“…A lack of such a system means that NCS children can neither look up the pronunciations of forgotten characters nor ask their NCS parents for help with character identification. In addition, it may be that children whose native language is Chinese (CS) learn to read and write in a more visual–spatial way, whereas those whose native language is alphabetic are more tuned into phonological coding as a way to learn new characters (e.g., Zhou & McBride, ). In the present study, we attempted to investigate phonological and visual–orthographic approaches Chinese literacy learning in Hong Kong among NCS and CS children separately in an effort to understand diversity in such learning.…”
Section: Theoretical Bases Of Learning To Read and Writementioning
confidence: 99%
See 1 more Smart Citation
“…A lack of such a system means that NCS children can neither look up the pronunciations of forgotten characters nor ask their NCS parents for help with character identification. In addition, it may be that children whose native language is Chinese (CS) learn to read and write in a more visual–spatial way, whereas those whose native language is alphabetic are more tuned into phonological coding as a way to learn new characters (e.g., Zhou & McBride, ). In the present study, we attempted to investigate phonological and visual–orthographic approaches Chinese literacy learning in Hong Kong among NCS and CS children separately in an effort to understand diversity in such learning.…”
Section: Theoretical Bases Of Learning To Read and Writementioning
confidence: 99%
“…Radical knowledge is widely recognised as effective for teaching of Chinese as well, so we included a radical knowledge method of teaching in the present study. Given some preliminary evidence of overreliance on phonological strategies in those whose first language/script is alphabetic (e.g., Zhou & McBride, ), we also tested the effectiveness of a phonological coding strategy for both groups in the current study. Finally, the typical approach to teaching Chinese character recognition in Hong Kong is the look–say method, so we included this simple memorisation technique as well.…”
Section: Theoretical Bases Of Learning To Read and Writementioning
confidence: 99%
“…A study comparing character processing skills among native and L2 learners in a bilingual international school in Hong Kong found that L2 learners lagged behind native learners in their Chinese reading development. In terms of working memory, both groups performed similarly for phonological working memory, but the L2 learners were weaker in their general working memory skills (Zhou & McBride, 2018). The association between weak working memory skills and poor reading indicates that L2 learners were somewhat deficient in their visuo-spatial working memory skills, thus preventing them from utilising both phonological and visual-spatial working memory efficiently for character recognition.…”
Section: Biscriptal Literacy Developmentmentioning
confidence: 90%
“…As oral language provides the foundation for literacy learning, stronger oral language proficiency is often associated with better reading skills (Zhou & McBride, 2018). In the case of L2 learners whose oral proficiency is still developing, their L2 reading development will somewhat be limited by their L2 oral proficiency (Swanson, Rosston, Gerber & Solari, 2008), particularly their vocabulary knowledge (Zhou & McBride, 2018).…”
Section: Phonological Encoding Through Pinyinmentioning
confidence: 99%
See 1 more Smart Citation